2016
DOI: 10.1158/1078-0432.ccr-15-1260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of EGFR Mutation Status in Matched Plasma and Tumor Tissue of NSCLC Patients from a Phase I Study of Rociletinib (CO-1686)

Abstract: Purpose: The evaluation of plasma testing for the EGFR resistance mutation T790M in NSCLC patients has not been broadly explored. We investigated the detection of EGFR activating and T790M mutations in matched tumor tissue and plasma, mostly from patients with acquired resistance to first-generation EGFR inhibitors.Experimental Design: Samples were obtained from two studies, an observational study and a phase I trial of rociletinib, a mutant-selective inhibitor of EGFR that targets both activating mutations an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
145
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 40 publications
18
145
3
2
Order By: Relevance
“…For the T790M detection, the sensitivity and specificity were 73% and 67% for the first technology and 81% and 58%, respectively, with a concordance between the platforms >90%. Another recent publication comparing BEAMing and cobas test showed a higher concordance between BEAMing plasma and tumor EGFR results than between cobas EGFR plasma and tumor (82% for activating mutations and 73% for T790M using BEAMing vs. 73% and 64%, respectively, using cobas plasma test) (54). NGS: the emerging of new drugs that target other genomic alterations than EGFR mutations have significantly increased the complexity of biomarker testing.…”
Section: Circulating Free Tumor Dnamentioning
confidence: 99%
“…For the T790M detection, the sensitivity and specificity were 73% and 67% for the first technology and 81% and 58%, respectively, with a concordance between the platforms >90%. Another recent publication comparing BEAMing and cobas test showed a higher concordance between BEAMing plasma and tumor EGFR results than between cobas EGFR plasma and tumor (82% for activating mutations and 73% for T790M using BEAMing vs. 73% and 64%, respectively, using cobas plasma test) (54). NGS: the emerging of new drugs that target other genomic alterations than EGFR mutations have significantly increased the complexity of biomarker testing.…”
Section: Circulating Free Tumor Dnamentioning
confidence: 99%
“…Mutations such as T790M can be found in both cfDNA and exosomal RNA/DNA, so combining these sources of nucleic acids increases sensitivity (27)(28)(29). This improves detection in patients with limited copies of circulating T790M in the cfDNA fraction, such as those with early stage disease or intrathoracic (M0/M1a) lung cancer patients (~25-30% of all newly diagnosed cases) (19). In addition to the increased sensitivity of mutation detection, it has been shown that mutations on exoNA correlate better to overall survival compared to cfDNA mutation analysis (27).…”
Section: Introductionmentioning
confidence: 99%
“…For the T790M mutation, the digital platforms outperformed the nondigital platforms. Recent publication comparing also BEAMing and cobas test, showed a higher positive percent agreement between BEAMing plasma and tumor results than cobas EGFR plasma and tumor results (82% for activating mutations and 73% for T790M using BEAMing vs 73% and 64%, respectively, using cobas plasma test) [45] . The emerge of new drugs that target other genomic alterations rather than EGFR mutations have significantly increase the complexity of biomarker testing.…”
Section: Circulating Free Tumor Dnamentioning
confidence: 98%